(untitled) (REMUNOM, 2025)
We can say that the conflict is already natural to the human being and is increasingly present in our personal life with family friends as in our professional life in the service environment. We will address in this article the management of these conflicts, with emphasis on the impacts caused by them, and the result that brings somehow in organizations. In this way we will address the problem of how interpersonal relationships and their conflicts influence the organizational environment. We can already say that it is important to know that the behavior of people influences the environment in which they live. Behaviors reflect company results, whether negative or positive, depending on the relationship within the industry. In the workplace everything can happen, that is, everything can influence people’s behavior and, as a consequence, influence in interpersonal relationships and probably in the results of companies, in every sense. The human being is made of the environment in which he lives, and which is generated by basic needs, which motivate or not to perform certain tasks, whether physiological needs or psychological needs, impetus to realize their potential, be in continuous self- development. We will address this issue by focusing on discussing conflicts, people, and organization, seeking to show the caudate impacts and how to make these conflicts in a way that becomes constructive for organizations. Keywords:People, relationship, organizational environment